CHANGING IN THE LANDSCAPE AND FORMATION OH TECHNOGENIC DEPOSITS IN PRESIDENTE PRUDENTE-SP - Pedro Miyazaki, Leda Correia; Silva, Erika Cristina Nesta [UNESP]; Nunes, Joao Osvaldo Rodrigues [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2017)
Technogenic deposits are originated by human activities on the environment. In this study approach considers man as a geological and geomorphological agent able causing changes in soil layers, directly or indirectly. The current research aims to study the formation of technogenic deposits in the northeast sector of Presidente Prudente, SP, especially in floodplains near the housing complex Jardim Humberto Salvador and Augusto de Paula. To achieve the objective were necessary to carry out literature surveys, field research to identify the process of soil uses and occupancys and collecting three samples of technogenic deposits in the study area. Historically, the deployment of such housing complex is associated with a pattern of land use and occupation of relief, without adequate planning, resulting in the formation of technogenic deposits in urban areas. In the case of textural, there was significant difference in composition of technogenic materials, identified as urbic and spoil, which allowed establishing relationships between natural and social aspects that shape the current landscape.
Keywords: landscape; land use; relief; technogenic deposits and geography